Method for catalytically decomposing lignin in supercritical ammonia by using high-entropy alloy catalyst
By using a high entropy alloy catalyst in supercritical ammonia to catalyze the decomposition of lignin, the problems of high energy consumption, low conversion rate and poor environmental friendliness in the prior art are solved, and the efficient, gentle and environmentally friendly lignin decomposition effect is achieved.
Patent Information
- Application Number
- CN202411816425.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-11
- Publication Date
- 2025-03-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing lignin decomposition technology has the problems of high energy consumption, low conversion rate and poor environmental friendliness, and it is difficult to develop a lignin decomposition technology with higher conversion rate, mild conditions and environmentally friendly.
High-entropy alloy catalysts are used in supercritical ammonia to catalyze the decomposition of lignin. High-entropy alloy catalysts are composed of iron salts, nickel salts, cobalt salts and manganese salts. They provide more active sites through the synergistic action of different metals and regulate the selectivity of the catalyst.
It has achieved efficient decomposition of lignin under mild conditions, high conversion rate, low energy consumption, high product selectivity, and the use of supercritical ammonia as a solvent to solve the problem of difficult separation of traditional organic solvents.
Smart Images

Figure BDA0005181924670000011 
Figure BDA0005181924670000051
Abstract
Description
Technical Field
[0001] The invention belongs to a method for decomposing lignin, and in particular relates to a method for catalytically decomposing lignin by using a high entropy alloy catalyst in supercritical ammonia. Background Art
[0002] Lignin is a natural polymer compound with high commercial value. Lignin is a biomacromolecule second only to cellulose in natural compound content, and is also the only major renewable source of aromatic rings; there are three main types of lignin basic structural units: p-hydroxybenzene structural unit (H type), guaiacyl structural unit (G type) and syringyl structural unit (S type). The details are as follows:
[0003]
[0004] Catalytic decomposition is the mainstream method for lignin recycling at present. The key to this reaction lies in the selection of reaction medium and catalyst. At present, most of the lignin decomposition methods reported in domestic and foreign literature are systems containing organic solvents (choline chloride, p-toluenesulfonic acid, aniline), which not only causes certain problems in product separation, but also poses challenges to the recycling of solvents.
[0005] In addition, the rational selection of catalysts is conducive to improving the conversion rate and selectivity of lignin degradation. At present, most of the lignin catalytic decomposition methods reported in domestic and foreign literature are metal catalysis. For example, the following:
[0006] CN117486679A discloses a method for preparing aromatic oxygen-containing compounds by pyrolysis of lignin by MOF perovskite catalysis. AA'B-MOF precursor perovskite catalyzes pyrolysis of lignin to obtain a liquid phase product containing phenolic compounds, which mainly includes phenols, guaiacols, syringols, aldehydes, esters, and ethers. The mass yield of the liquid phase is ≥35%, and the total selectivity is ≥80%. However, lignin needs to be pyrolyzed at 200-500°C, and the energy consumption is relatively high.
[0007] CN117925265A discloses a method for directly hydrogenating and liquefying lignin to produce oil by using a catalyst containing molybdenum or iron in a lignin-based circulating solvent containing a large amount of polycyclic aromatic compounds. The method uses heterogeneous MoS2, MoO3, Mo2C or FeS2 as a catalyst and hydrogen as a reducing agent to directly hydrogenate and liquefy lignin in a lignin-based circulating solvent to produce oil, and the fraction above 225°C in the product oil can be used as a lignin-based circulating solvent. The method has a lignin conversion rate of about 90wt%, an oil yield of about 84wt%, a PAA yield of about 6wt%, and a polycyclic aromatic compound yield of about 28wt%, but the method still requires complex post-processing operations such as distillation, and the energy consumption is also relatively large.
[0008] Therefore, how to develop a lignin decomposition technology with higher conversion rate, mild conditions and environmental friendliness is an urgent problem to be solved in this field. Summary of the invention
[0009] The technical problem to be solved by the present invention is to provide a method for catalytically decomposing lignin using a high entropy alloy catalyst in supercritical ammonia.
[0010] In order to solve the above technical problems, the present invention provides a high entropy alloy catalyst, which is a supported catalyst prepared from a metal salt and a carrier, wherein the metal salt is composed of an iron salt, a nickel salt, a cobalt salt and a manganese salt, and the sum of the weights of iron, nickel, cobalt and manganese accounts for 10-20% of the total weight of the supported catalyst, and the weights of iron, nickel, cobalt and manganese respectively meet the following conditions: ≥ 2% of the total weight of the supported catalyst, and ≤ 5% of the total weight of the supported catalyst. The carrier is, for example, graphene oxide.
[0011] As an improvement of the high entropy alloy catalyst of the present invention:
[0012] Co accounts for 2.5-2.7wt% (preferably 2.65wt%) of the total weight of the supported catalyst, Fe accounts for 2.4-2.6wt% (preferably 2.51wt%) of the total weight of the supported catalyst, Ni accounts for 2.5-2.7wt% (preferably 2.65wt%) of the total weight of the supported catalyst, and Mn accounts for 2.4-2.6wt% (preferably 2.5wt%) of the total weight of the supported catalyst.
[0013] The present invention also provides a method for preparing the high entropy alloy catalyst, comprising the following steps:
[0014] ① Dissolve the four metal salts of cobalt, iron, nickel and magnesium in ethylene glycol to obtain a metal salt solution;
[0015] Adding graphene oxide as a carrier into an ethylene glycol solution and ultrasonicating the solution to obtain a graphene oxide dispersion;
[0016] The metal salt solution is added to the graphene oxide dispersion and reacted under reflux conditions for 4±0.5h; the mixed solution obtained by the reflux reaction is then centrifuged, and the solid obtained by centrifugation is vacuum dried to obtain a precursor;
[0017] ②. The precursor is calcined at 900±50°C for 1±0.1h to obtain a high entropy alloy catalyst.
[0018] Note: Calcination was carried out in air atmosphere.
[0019] As an improvement of the preparation method of the high entropy alloy catalyst of the present invention:
[0020] The metal salt is a nitrate or chloride of a metal.
[0021] As a further improvement of the preparation method of the high entropy alloy catalyst of the present invention, in the step ①:
[0022] Ultrasonication time is 10 to 30 minutes;
[0023] Reflux temperature is 170±20℃;
[0024] Use 25-35 ml of ethylene glycol for every 0.12 mmol of metal salt and 140-160 ml of ethylene glycol for every 60 mg of graphene oxide;
[0025] The centrifugal speed is 1000±100rpm / min, the vacuum drying temperature is 60-90°C, and the time is 12-24h.
[0026] As a further improvement of the preparation method of the high entropy alloy catalyst of the present invention:
[0027] ①, Weigh 0.03mmol each of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O, and MnCl2·4H2O, add these four metal salts into 30ml ethylene glycol to dissolve, and obtain metal salt solution;
[0028] Weigh 60 mg of graphene oxide powder and add it to 150 ml of ethylene glycol for ultrasonication to obtain a graphene oxide dispersion;
[0029] The metal salt solution is added to the graphene oxide dispersion and refluxed for 4 hours; the mixed solution obtained by the reflux reaction is centrifuged, and the solid obtained by the centrifugation is vacuum dried at 60° C. for 12 hours to obtain a precursor;
[0030] ②. Calcine the precursor at 900°C in air for 1 hour to obtain a high entropy alloy catalyst.
[0031] The present invention also provides a method for catalytically decomposing lignin, comprising the following steps:
[0032] 1) Add lignin and a high entropy alloy catalyst into an autoclave, replace the autoclave with an inert gas (such as nitrogen, argon, etc.), then fill the autoclave with liquid ammonia, and stir continuously to make the liquid ammonia and lignin fully contact; the mass of the lignin is 10-20wt% (preferably 12-13wt%) of the mass of the liquid ammonia, and the mass of the catalyst is 1-9wt% (preferably 8-9wt%) of the mass of the liquid ammonia;
[0033] Then, the autoclave temperature-raising program is started, the temperature is raised to the reaction temperature according to the set temperature-raising program, and the pressure is raised until the ammonia reaches a supercritical state to react (high temperature and high pressure reaction);
[0034] Note: The purpose of replacing the inert gas (such as nitrogen) in the autoclave cavity is to exhaust the air in the reactor to prevent product oxidation and side reactions;
[0035] 2) After the reaction is completed, the temperature and pressure are reduced (cooled to room temperature, reduced to normal pressure); then solid-liquid separation is performed (the solid-liquid mixture is filtered, etc.), and the separated liquid is the lignin decomposition product.
[0036] Note: The solid separated is the catalyst and a small amount of undecomposed lignin.
[0037] The decomposition products of lignin are polycyclic aromatic compounds, mainly phenol and aniline compounds.
[0038] As an improvement of the method for catalytically decomposing lignin of the present invention: the reaction temperature is 134-145° C., the reaction pressure is 11.3-12.5 MPa, and the reaction time is 4-6 hours.
[0039] As a further improvement of the method for catalytic decomposition of lignin of the present invention, the temperature rising program of the autoclave is: the temperature rising rate below 100°C is 5°C / min, the temperature rising rate from 100°C to less than 120°C is 2°C / min, the temperature rising rate from 120°C to less than 130°C is 1°C / min, and the temperature rising rate from 130°C to the reaction temperature is 0.5°C / min.
[0040] As a further improvement of the method for catalytically decomposing lignin of the present invention, the lignin is at least any one of the following: alkali lignin, dealkalized lignin, and lignin sulfonate.
[0041] The present invention loads four metals, Co, Fe, Ni and Mn, onto a carrier via metal salts. The alloy catalyst can provide more active sites through the synergistic effect of different metals. By changing the ratio of each metal element in the alloy, the selectivity of the catalyst can be effectively adjusted, which has high practical value.
[0042] The present invention has developed a method for decomposing lignin with supercritical ammonia, which uses supercritical ammonia as a solvent. While serving as a solvent, supercritical ammonia also serves as an excellent nitrogen source. The present invention solves the problem of difficulty in separating in the later stage of the system with traditional organic solvent as solution by using supercritical ammonia as a solvent; the addition of high entropy alloy catalyst solves the problem of conversion rate and selectivity in the reaction.
[0043] Compared with the prior art, the present invention has the following technical advantages:
[0044] (1) The method of catalytically decomposing lignin in supercritical ammonia using a high entropy alloy catalyst of the present invention does not require excessively high temperatures, saves energy, has a high raw material conversion rate, and has a fast reaction speed.
[0045] That is, the decomposition environment required by the present invention is carried out under the condition that a high entropy alloy catalyst is added to supercritical ammonia.
[0046] (2) The reaction medium (supercritical ammonia) of the present invention is a supercritical fluid, which has the advantages of being green, efficient and clean. In addition, near the critical point, slight changes in pressure and temperature can cause a large change in fluid density, thereby causing a large change in solubility, which facilitates the regulation of reaction conditions.
[0047] (3) The high entropy alloy catalyst preparation method of the present invention is simple and reusable.
[0048] (4) The lignin catalytic decomposition method provided by the present invention is simple to operate, has a high lignin decomposition rate, and a low degree of polymerization of the product. DETAILED DESCRIPTION
[0049] The present invention is further described below in conjunction with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0050] Catalyst Example 1: Preparation of a high entropy alloy catalyst, the following steps are performed in sequence:
[0051] ①, Weigh 0.03mmol each of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O, and MnCl2·4H2O, add these four metal salts into 30ml of ethylene glycol, and stir to fully dissolve them to obtain a metal salt solution;
[0052] Weigh 60 mg of graphene oxide powder and add it to 150 ml of ethylene glycol and ultrasonicate for 20 min to obtain a graphene oxide dispersion;
[0053] The metal salt solution was added to the graphene oxide dispersion and refluxed at 170°C for 4 hours; the mixed solution obtained by the reflux reaction was centrifuged at a speed of 1000 rpm / min for 5 minutes, and the solid obtained by centrifugation was vacuum dried at 60°C for 12 hours to obtain a precursor, wherein the mass fraction of Co was 2.65wt%, Fe was 2.51wt%, Ni was 2.65wt%, and Mn was 2.5wt%.
[0054] ②. Calcine the precursor at 900°C in air for 1 hour to obtain a high entropy alloy catalyst.
[0055] Example 1: Decomposing alkali lignin in supercritical ammonia using a high entropy alloy catalyst, the following steps are performed in sequence:
[0056] 1) Reaction:
[0057] ①. Weigh 1.5 g of raw alkali lignin and 1 g of the prepared high entropy alloy catalyst (obtained in Catalyst Example 1), pour them into a 100 mL reactor, and close the reactor.
[0058] ②. Use nitrogen to replace the gas in the autoclave several times, and then fill it with 12g of liquid ammonia; and stir continuously to ensure that the liquid ammonia and lignin are fully in contact.
[0059] ③. Start the temperature rise program of the autoclave: the temperature rise rate below 100°C is 5°C / min, the temperature rise rate from 100 to less than 120°C is 2°C / min, the temperature rise rate from 120 to less than 130°C is 1°C / min, and the temperature rise rate from 130°C to reaction temperature (134°C) is 0.5°C / min.
[0060] Then, the reaction was stirred for 4 hours at a reaction temperature of 134° C. and a reaction pressure of 11.3 MPa (the gas expands when the temperature rises, and the pressure increases accordingly).
[0061] 2) After the reaction is completed, the pressure is released and the autoclave is opened, and the liquid ammonia becomes gas and leaves the system. When the reaction liquid is cooled to room temperature, the cooled reaction liquid is filtered to obtain a filtrate and a filter residue respectively; the filtrate is collected to obtain a product, and the components of the product are mainly phenylamine, guaiacamine, and syringamine.
[0062] The catalyst and a small amount of undecomposed lignin in the filter residue are separated. The lignin can be dissolved by a suitable solvent to separate the catalyst from the lignin. For example, an aqueous NaOH solution (PH>10.5) can be used.
[0063] The conversion rate was 92.6% and the selectivity was 82.2%.
[0064] Conversion rate 1-[(m filter residue-m catalyst) / m raw material alkali lignin],
[0065]
[0066] Note: The separated catalyst can be reused after conventional washing. After being reused three times, there was no significant decrease in conversion rate and selectivity.
[0067] Embodiment 2 to Embodiment 7
[0068] The reaction temperature was changed, and other operations were the same as in Example 1 to obtain Examples 2 to 7. The process parameters and reaction results are shown in Table 1.
[0069] Table 1, data of Examples 2 to 7
[0070] Example Temperature(℃) Conversion rate Selectivity 1 134 92.6% 82.2% 2 135 92.7% 82.3% 3 137 92.8% 82.5% 4 139 93.0% 82.6% 5 141 92.9% 82.8% 6 143 92.7% 82.5% 7 145 92.5% 82.4%
[0071] Embodiment 8 to Embodiment 13
[0072] The reaction pressure was changed, and other operations were the same as those in Example 4 to obtain Examples 8 to 13. See Table 2 for process parameters and reaction results.
[0073] Table 2, data of Examples 8 to 13
[0074] Example Pressure(Mpa) Conversion rate Selectivity 8 11.5 93.1% 82.6% 9 11.7 93.3% 82.8% 10 11.9 93.4% 82.9% 11 12.1 93.4% 83.0% 12 12.3 93.2% 82.8% 13 12.5 93.0% 82.6%
[0075] Example 14: The "alkali lignin" in Example 1 is replaced with "de-alkali lignin", and the amount used remains unchanged; the rest is the same as Example 1.
[0076] The results obtained were as follows: the conversion rate of alkali lignin was 90.6% and the selectivity was 80.5%.
[0077] Example 15: The "alkali lignin" in Example 1 is replaced with "lignin sulfonate (sodium lignin sulfonate)", and the amount used remains unchanged; the rest is the same as Example 1.
[0078] The results obtained were as follows: the conversion rate of alkali lignin was 89.2% and the selectivity was 81.2%.
[0079] Comparative Example 1
[0080] The amount of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O and MnCl2·4H2O in Catalyst Example 1 was changed from "0.03 mmol each" to "0.015 mol each", that is, the weights of iron, nickel, cobalt and manganese were 1.26wt%, 1.33wt%, 1.33wt% and 1.25wt% of the total weight of the supported catalyst, respectively.
[0081] The rest was the same as in Catalyst Example 1, and the obtained product was named Catalyst A.
[0082] The "high entropy alloy catalyst (obtained from Catalyst Example 1)" in Example 1 was replaced with Catalyst A, the dosage remained unchanged, and the rest was the same as Example 1.
[0083] The results obtained were as follows: the conversion rate of alkali lignin was 60.9% and the selectivity was 50.5%.
[0084] Comparative Example 2
[0085] The amount of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O and MnCl2·4H2O in Catalyst Example 1 was changed from "0.03 mmol each" to "0.06 mol each", that is, the weights of iron, nickel, cobalt and manganese were 5.02wt%, 5.3wt%, 5.3wt% and 5.0wt% of the total weight of the supported catalyst, respectively.
[0086] The rest was the same as in Catalyst Example 1, and the obtained product was named Catalyst B.
[0087] The "high entropy alloy catalyst (obtained from Catalyst Example 1)" in Example 1 was replaced with Catalyst B, the dosage remained unchanged, and the rest was the same as Example 1.
[0088] The results obtained were as follows: the conversion rate of alkali lignin was 90.8% and the selectivity was 82.3%.
[0089] Comparative Example 3-1
[0090] The "amounts of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O, and MnCl2·4H2O are each 0.03 mmol" in Catalyst Example 1 was changed to "CoCl2·6H2O 0.04 mmol, Fe(NO3)·9H2O 0.04 mmol, NiCl2·6H2O 0.04 mmol", and the rest were the same as Catalyst Example 1. The resultant was named Catalyst C.
[0091] The "high entropy alloy catalyst (obtained from Catalyst Example 1)" in Example 1 was replaced with Catalyst C, the dosage remained unchanged, and the rest was the same as Example 1.
[0092] The results obtained were as follows: the conversion rate of alkali lignin was 63.2% and the selectivity was 72.3%.
[0093] Comparative Example 3-2
[0094] The "amounts of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O, and MnCl2·4H2O are 0.03 mmol each" in Catalyst Example 1 was changed to "CoCl2·6H2O 0.04 mmol, Fe(NO3)·9H2O 0.04 mmol, and MnCl2·4H2O 0.04 mmol", and the rest was the same as Catalyst Example 1. The resultant was named Catalyst D;
[0095] The "high entropy alloy catalyst (obtained from Catalyst Example 1)" in Example 1 was replaced with Catalyst D, the dosage remained unchanged, and the rest was the same as Example 1.
[0096] The results obtained were as follows: the conversion rate of alkali lignin was 61.2% and the selectivity was 68.3%.
[0097] Comparative Example 3-3
[0098] The "amounts of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O, and MnCl2·4H2O are 0.03 mmol each" in Catalyst Example 1 is changed to "Fe(NO3)·9H2O 0.04 mmol, NiCl2·6H2O 0.04 mmol, MnCl2·4H2O 0.04 mmol", and the rest is the same as Catalyst Example 1. The resultant is named Catalyst E;
[0099] The "high entropy alloy catalyst (obtained from Catalyst Example 1)" in Example 1 was replaced with Catalyst E, the dosage remained unchanged, and the rest was the same as Example 1.
[0100] The results obtained were as follows: the conversion rate of alkali lignin was 59.6% and the selectivity was 70.5%.
[0101] Comparative Examples 3-4
[0102] The "amounts of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O, and MnCl2·4H2O are 0.03 mmol each" in Catalyst Example 1 is changed to "CoCl2·6H2O 0.04 mmol, NiCl2·6H2O 0.04 mmol, MnCl2·4H2O 0.04 mmol", and the rest is the same as Catalyst Example 1. The resultant is named Catalyst F;
[0103] The "high entropy alloy catalyst (obtained from Catalyst Example 1)" in Example 1 was replaced with Catalyst F, the dosage remained unchanged, and the rest was the same as Example 1.
[0104] The results obtained were as follows: the conversion rate of alkali lignin was 61.3% and the selectivity was 55.2%.
[0105] Comparative Example 4
[0106] The "amounts of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O, and MnCl2·4H2O are 0.03 mmol each" in Catalyst Example 1 was changed to "CoCl2·6H2O 0.024 mmol, Fe(NO3)·9H2O 0.024 mmol, MnCl2·4H2O 0.024 mmol, NiCl2·6H2O 0.024 mmol, CuCl2 0.024 mmol", and the rest was the same as Catalyst Example 1. The resultant was named Catalyst E;
[0107] The "high entropy alloy catalyst (obtained from Catalyst Example 1)" in Example 1 was replaced with Catalyst E, the dosage remained unchanged, and the rest was the same as Example 1.
[0108] The results obtained were as follows: the conversion rate of alkali lignin was 80.3% and the selectivity was 84.2%.
[0109] Finally, it should be noted that the above examples are only some specific embodiments of the present invention. Obviously, the present invention is not limited to the above embodiments, and there are many variations. All variations that can be directly derived or associated with the content disclosed by a person skilled in the art should be considered as the protection scope of the present invention.
Claims
1. A high entropy alloy catalyst, characterized in that: The high entropy alloy catalyst is a supported catalyst prepared from a metal salt and a carrier, wherein the metal salt is composed of an iron salt, a nickel salt, a cobalt salt and a manganese salt, the sum of the weights of iron, nickel, cobalt and manganese accounts for 10-20% of the total weight of the supported catalyst, and the weights of iron, nickel, cobalt and manganese respectively meet the following conditions: ≥2% of the total weight of the supported catalyst, and ≤5% of the total weight of the supported catalyst.
2. The high entropy alloy catalyst according to claim 1, characterized in that: Co accounts for 2.5-2.7 wt% of the total weight of the supported catalyst, Fe accounts for 2.4-2.6 wt% of the total weight of the supported catalyst, Ni accounts for 2.5-2.7 wt% of the total weight of the supported catalyst, and Mn accounts for 2.4-2.6 wt% of the total weight of the supported catalyst.
3. A method for preparing a high entropy alloy catalyst, characterized in that The steps include: ① Dissolve the four metal salts of cobalt, iron, nickel and magnesium in ethylene glycol to obtain a metal salt solution; Adding graphene oxide as a carrier into an ethylene glycol solution and ultrasonicating the solution to obtain a graphene oxide dispersion; The metal salt solution is added to the graphene oxide dispersion and reacted under reflux conditions for 4±0.5h; the mixed solution obtained by the reflux reaction is then centrifuged, and the solid obtained by centrifugation is vacuum dried to obtain a precursor; ②. The precursor is calcined at 900±50°C for 1±0.1h to obtain a high entropy alloy catalyst.
4. The method for preparing a high entropy alloy catalyst according to claim 3, characterized in that: The metal salt is a nitrate or chloride of a metal.
5. The method for preparing a high entropy alloy catalyst according to claim 3 or 4, characterized in that In step ①: Ultrasonication time is 10 to 30 minutes; Reflux temperature is 170±20℃; Use 25-35 ml of ethylene glycol for every 0.12 mmol of metal salt and 140-160 ml of ethylene glycol for every 60 mg of graphene oxide; The centrifugal speed is 1000±100rpm / min, the vacuum drying temperature is 60-90°C, and the time is 12-24h.
6. The method for preparing a high entropy alloy catalyst according to any one of claims 3 to 5, characterized in that: ①, Weigh 0.03mmol each of CoCl2·6H2O, Fe(NO3)·9H2O, NiCl2·6H2O, and MnCl2·4H2O, add these four metal salts into 30ml ethylene glycol to dissolve, and obtain metal salt solution; Weigh 60 mg of graphene oxide powder and add it to 150 ml of ethylene glycol for ultrasonication to obtain a graphene oxide dispersion; The metal salt solution is added to the graphene oxide dispersion and refluxed for 4 hours; the mixed solution obtained by the reflux reaction is centrifuged, and the solid obtained by the centrifugation is vacuum dried at 60° C. for 12 hours to obtain a precursor; ②, calcine the precursor at 900℃ in air for 1h; A high entropy alloy catalyst was obtained.
7. A method for catalytically decomposing lignin, characterized in that The following steps are involved: 1) Add lignin and a high entropy alloy catalyst into an autoclave, replace the autoclave with an inert gas, and then fill the autoclave with liquid ammonia, and stir continuously to make the liquid ammonia and lignin fully contact; the mass of the lignin is 10-20wt% of the mass of the liquid ammonia, and the mass of the catalyst is 1-9wt% of the mass of the liquid ammonia; Then, the autoclave temperature raising program is started, the temperature is raised to the reaction temperature according to the set temperature raising program, and the pressure is raised until the ammonia reaches a supercritical state for reaction; 2) After the reaction is completed, the temperature and pressure are lowered; then solid-liquid separation is performed, and the separated liquid is the lignin decomposition product.
8. The method for catalytically decomposing lignin according to claim 7, characterized in that: The reaction temperature is 134-145°C, the reaction pressure is 11.3-12.5 MPa, and the reaction time is 4-6 hours.
9. The method for catalytically decomposing lignin according to claim 8, characterized in that The temperature rise program of the autoclave is as follows: the temperature rise rate below 100°C is 5°C / min, the temperature rise rate between 100°C and less than 120°C is 2°C / min, the temperature rise rate between 120°C and less than 130°C is 1°C / min, and the temperature rise rate between 130°C and the reaction temperature is 0.5°C / min.
10. The method for catalytically decomposing lignin according to claim 9, characterized in that The lignin is at least any one of the following: alkali lignin, dealkalized lignin, and lignin sulfonate.
Citation Information
Patent Citations
Method for preparing aryl oxygen-containing compound by catalytic pyrolysis of lignin through MOF perovskite
CN117486679A
Method for preparing oil through catalytic hydrogenation and direct liquefaction of lignin
CN117925265A
Nickel-based catalyst for ammonia decomposition and preparation method and application thereof
CN101780413A
Method for core-shell catalyst to convert bagasse lignin into phenol compound
CN105481655A
High-entropy oxide and high-entropy alloy catalyst as well as preparation method and application of high-entropy oxide and high-entropy alloy catalyst
CN115845858A